Q-angle and postural stability: a review of the relationship and implications for fall risk - Komang Tri Yudartha Widnyana; A A I Ayesa Febrinia Adyasputri; I Dewa Gede Alit Kamayoga (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Introduction: One of the condition common types of muscular distortion is retrieved Q-angle and postural stability. The function lower extremities with all the structures assist postural stability in most static postures and dynamic movements or activities. The changes in the Q-angle and postural stability contribute to the development risk of falling. This study aimed to examine the relationship and implications of Q-angle and postural stability for fall risk. Methods: This study uses a literature review by conducting data through an electronic database such as Pedro, Pubmed, and Google Scholar. They had discussed approximately Q-angle, postural stability, and fall prevention with selection by inclusion and exclusion criteria. Results: We discovered three research related articles. The studies examined the relationship and implications of Q-angle and postural stability for fall risk. The results of those studies, Q-angle and postural stability had a correlate and implication for fall risk. Conclusion: Q-angle and postural stability are related to the risk of falling. The risk of falling can be decreased by reducing the Q-angle and improving postural stability. Additionally, it can be achieved through exercise or orthotics to helps reduce the risk of falls, which will eventually avoid injuries.